2013
DOI: 10.1038/modpathol.2012.146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microvascular density in Barrett's associated neoplasia

Abstract: Angiogenesis has an important role in the carcinogenesis of esophageal adenocarcinoma, however, the diagnostic and prognostic utility of microvascular density counts have not been clinically established. The aim of this study is to assess the correlation between microvascular density and disease progression of non-dysplastic Barrett's esophagus, low-grade dysplasia, high-grade dysplasia and invasive carcinoma in the superficial aspects of the tissue. Archival histological specimens from two referral centers fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Szafranowski et al reported a significant increase in microvessel density identified with CD34 and CD105 in laryngeal cancer and dysplasia when compared to the healthy control group [10]. Prior research on microvessel density in intraepithelial lesions of the oesophagus and cervix confirmed an increased vessel number associated with the transformation from intraepithelial lesions to invasive cancers [11, 12]. CD31 and CD34 are most commonly utilised as endothelial markers in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Szafranowski et al reported a significant increase in microvessel density identified with CD34 and CD105 in laryngeal cancer and dysplasia when compared to the healthy control group [10]. Prior research on microvessel density in intraepithelial lesions of the oesophagus and cervix confirmed an increased vessel number associated with the transformation from intraepithelial lesions to invasive cancers [11, 12]. CD31 and CD34 are most commonly utilised as endothelial markers in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in microvascular density also has been described across the metaplasia- dysplasia-carcinoma sequence, potentially contributing to the observed phenomenon. 22 Histologic studies also have described dilated ducts and glands that are surrounded, compressed, and deformed by a fibrotic lamina propria. 20,21 These cystic structures are thought to arise from compression of their glandular outlets by the collagen-rich tissue or by proliferating dysplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increased microvessel density in the progression from NDBE to LGD and HGD was recently reported based on ex vivo pathology specimens 12 . Narrow band imaging (NBI) 13, 14 and confocal laser endomicroscopy (CLE) 15, 16 were used to investigate microvascular changes as a potential marker for dysplasia.…”
Section: Introductionmentioning
confidence: 81%